PENGARUH ASET PAJAK TANGGUHAN, KONSENTRASI KEPEMILIKAN, DAN UKURAN PERUSAHAAN TERHADAP MANAJEMEN LABA - Siti Aminah; Zulaikha Zulaikha (Diponegoro Journal of Accounting, 2019)
This study aims to examine whether deferred tax assets, ownership concentration and firm size affect on earnings management. Earnings management is an activity of manipulating earning information in the financial statements performed by corporate managers with the aim to protect the interests of the company and gain profits. Population in this study are companies that is consistently included in LQ45 and listed on the Indonesia Stock Exchange during the period 2015-2017. Samples in this research are 87 companies, that were collected by using purposive sampling method based on certain criteria. The method of analysis used is multiple regression. The results show that deferred tax assets have significant positive effect to earnings management. These results prove that the higher company’s accruals and deferred tax liabilities cause the greater possibility of the company's earnings management. On the other hand, ownership concentration and firm size have significant negative effects to earnings management. This indicates that the larger foreign ownership or firm size cause the possibility of companies in the earnings management can be minimized.